Flexible and modular virtual scanning probe microscope - Tracey, J.; Federici Canova, F.; Keisanen, O.; Gao, D.; Spijker, P.; Reischl, Bernhard; Foster, A. (Elsevier, 2015)
Non-contact Atomic Force Microscopy (NC-AFM) is an experimental technique capable of imaging almost any surface with atomic resolution, in a wide variety of environments. Linking measured images to real understanding of system properties is often difficult, and many studies combine experiments with detailed modelling, in particular using virtual simulators to directly mimic experimental operation. In this work we present the PyVAFM, a flexible and modular based virtual atomic force microscope capable of simulating any operational mode or set-up. Furthermore, the PyVAFM is fully expandable to allow novel and unique set-ups to be simulated, finally the PyVAFM ships with fully developed documentation and tutorial to increase usability.